The Good Life Almanac - Smalley, Ruth (Appalachian State University, 1975)
Published in 1975, this is an almanac of stories gathered from the Solway, Tennessee community as a microcosm of the Appalachian region during a period of transition. Written to showcase the stories and folklore passed on in the mountains, the tales chosen are typical of the nineteenth century. Stories talk about the dependence on water transportation, the excitement of the coming railroad, the self-contained nature of community recreation, and the interdependence and independence of small community's daily life. In addition to stories, traditional regional recipes are included in order to demonstrate further what it was like to live in the mountains.